Repatriation: what do we know and where do we go from here. Issue 1 (2nd January 2018) - Chiang, Flora F. T.; van Esch, Emmy; Birtch, Thomas A.; Shaffer, Margaret A.
Abstract: The unparalleled growth in multinational corporations in recent decades has witnessed a commensurate rise in the deployment of expatriates to foreign subsidiaries and their subsequent repatriation. However, despite considerable progress in our understanding of the expatriation phase of international assignments, the literature on repatriation remains fragmented and incomplete. Plagued with problematic re-adjustments, high turnover rates, and a range of other obstacles, there is an urgent need for an improved understanding of repatriation. This study systematically reviews the repatriation literature over the previous four decades, identifies its major themes, gaps and limitations, and provides a framework that consolidates the literature and prompts future work in several important new directions.